THE ROLE OF FK3 INDEPENDENT TRADE UNIONS IN RESOLVING WORKERS' AND MANAGEMENT CONFLICT DISPUTES BIPATRITLY IN PT. INDAH KIAT PULP & PAPER TBK - Dominggo Subandrio; Ahmad Toni; Riska Ferdiana (SEAN Institute, 2022)
The Industrial Sector after the Covid-19 pandemic that has hit the world since the end of 2019, is a nightmare for the entire industrial sector. Industry began to rise to economic growth after the pandemic, with a slow influx of investment and a large expansion of investment into the regions that were improving the industry's state. The development of the business world is influenced by human resources, which is one of the most important components that can streamline the achievement of one company's business goals. The relationship between employers and workers in work relations is expected to be harmonious to achieve improvement, work productivity and welfare. The government guarantees workers freedom of association and assembly in a union forum. The FK3 Independent Workers Union is the only trade union in PT. Beautiful Tips Pulp & Paper. The issue of Industrial relations has always been a never-ending conversation between workers, trade unions and employers to be studied on labor bipatrit . Management and workers sometimes do not escape a problem that often occurs in the field or a phenomenon that often occurs in the company environment. The employment relationship between workers and employers is not always harmonious, there are disagreements in responding to labor law. The purpose of the study became a learning material for researchers to understand the role of trade unions and the Communication Forum (FK3) in dispute resolution . conflicts between workers and management bipatrit in PT. Beautiful Tips Pulp & Paper Tbk. This research is based on several observations studied by researchers, to discover the existence of the Independent Trade Union Employee Welfare Communication Forum (FK3). This research uses a descriptive qualitative approach method to describe some of the analysis obtained from the research object in a valid source obtained. Qualitative case studies as research that uses empirical evidence from one or more.